Bacillus subtilis, a potential biocontrol agent for the management of coriander wilt - C Ushamalini, S Aswathi, (Journal of Spices and Aromatic Crops, 2017)
Coriander is an important spice crop affected by wilt caused by Fusarium oxysporum f. sp. corianderii. Two trials were conducted to evaluate the efficacy of Bacillus subtilis for the management of wilt under glass house condition. The results of the trials indicated that, among the various treatments, seed treatment with talc formulation of Bacillus subtilis (10g/kg of seed) along with soil application (2.5 kg/ha) as basal and top dressing at 30 and 45 days after sowing was effective in reducing the wilt incidence (14.59%) compared to control (32.68% ).